AtHESPERIN: a novel regulator of circadian rhythms with poly(A)-degrading activity in plants. Issue 1 (2nd January 2016) - Delis, Costas; Krokida, Afrodite; Tomatsidou, Anastasia; Tsikou, Daniela; Beta, Rafailia A.A.; Tsioumpekou, Maria; Moustaka, Julietta; Stravodimos, Georgios; Leonidas, Demetres D.; Balatsos, Nikolaos A. A.; Papadopoulou, Kalliope K.
ABSTRACT: We report the identification and characterization of a novel gene, AtHesperin ( AtHESP ) that codes for a deadenylase in Arabidopsis thaliana . The gene is under circadian clock-gene regulation and has similarity to the mammalian Nocturnin . AtHESP can efficiently degrade poly(A) substrates exhibiting allosteric kinetics. Size exclusion chromatography and native electrophoresis coupled with kinetic analysis support that the native enzyme is oligomeric with at least 3 binding sites. Knockdown and overexpression of AtHESP in plant lines affects the expression and rhythmicity of the clock core oscillator genes TOC1 and CCA1 . This study demonstrates an evolutionary conserved poly(A)-degrading activity in plants and suggests deadenylation as a mechanism involved in the regulation of the circadian clock. A role of AtHESP in stress response in plants is also depicted.